2017
DOI: 10.1111/cpr.12422
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding PANDAR as a novel biomarker in human cancer: A systematic review

Abstract: Objectives: Long non-coding RNAs (lncRNAs) are characterized as a group of RNAs that more than 200 nucleotides in length and have no protein-coding function. More and more evidences provided that lncRNAs serve as key molecules in the development of cancer. Deregulation of lncRNAs functions as either oncogenes or tumour suppressor genes in various diseases. Recently, increasing studies about PANDAR in cancer progression were reported. In our review, we will focus on the current research on the character of PAND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Consistent with our research, previous studies con rmed that some lncRNAs were signi cantly related to clinical traits of tumors. For example, Mahdi's research showed that there was a positive correlation between lncRNA and TNM stage [32]. Thus, we speculated that this prognostic signature can be used as a supplement to colon cancer TNM classi cation and staging.…”
Section: Discussionmentioning
confidence: 90%
“…Consistent with our research, previous studies con rmed that some lncRNAs were signi cantly related to clinical traits of tumors. For example, Mahdi's research showed that there was a positive correlation between lncRNA and TNM stage [32]. Thus, we speculated that this prognostic signature can be used as a supplement to colon cancer TNM classi cation and staging.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, PANDA silencing results in cell cycle arrest in G1/ S transition through upregulation of cyclin-dependent kinase inhibitor p18 in U2OS osteosarcoma cell line. Depletion of PANDA leads to cell death of doxorubicin treated cells through upregulation of apoptotic activators APAF1, BIK, FAS, and LRDD [249,250]. Taken together, these findings imply that inhibition of PANDA might serve as a therapeutic intervention to induce cell cycle arrest and apoptosis in osteosarcoma.…”
Section: Lncrnas As Therapeutic Targets In Osteosarcomamentioning
confidence: 80%
“…Indeed, potential diagnostic and prognostic biomarkers for NSCLC are increasingly being reported such as plasma linc00152 [ 20 ], circulating lncRNA PCAT6 [ 21 ], AFAP1-AS1 [ 22 ], HOTAIR [ 23 , 24 ], lncRNA 00312 and 00673 [ 25 ] for diagnosis, and lncRNA CASC9.5 [ 26 ] plus LINC00968 [ 27 ] for NSCLC prognosis. In addition, PANDAR [ 28 ] and LncRNA RP11 713B9.1 [ 29 ] were also described as promising biomarkers and potential therapeutic targets for NSCLC. Patients with NSCLC, advanced nonsquamous NSCLC, and squamous cell histology were suggested to test for EGFR mutations, ALK rearrangements, and ROS1 fusions [ 30 ].…”
Section: Introductionmentioning
confidence: 99%